Evidence from gas-rich ultramafic xenoliths for Superplume-derived recycled volatiles in the East African sub-continental mantle - Sæmundur A. Halldórsson; Hilton, David R.; Marshall, Edward W.; Ranta, Eemu; Ingvason, Andri; Chakraborty, Subrata; Robin, Jóhann Gunnarsson; Rasmussen, Maja B.; Gibson, Sally A.; Ono, Shuhei; Scarsi, Paolo; Abebe, Tsegeye; et al. (Chemical geology, 2022)
Volatile-rich fluids are believed to play a key role in the metasomatic enrichment of the East African sub-continental lithospheric mantle (SCLM), but limited data is available on key volatile tracers such as CO2 and N2. We report new CO2 and N2 isotope and relative abundance data in exceptionally gas-rich mantle peridotite and pyroxenite xenoliths from nine localities throughout the eastern branch of the East African Rift System (EARS). Importantly for our study, the xenolith localities straddle the transition between continental and oceanic lithosphere. In addition, we report major and trace element contents together with oxygen isotopes on host crystals and bulk multiple sulfur isotope data on select pyroxene crystals from the same xenolith suite. These new data are interpreted alongside previously published He, Ne and Ar isotope and relative abundance data. Pyroxenite xenoliths formed from the infiltration and crystallization of mafic melts in the lithospheric mantle. This was followed by fluids fracturing through the pyroxenites leaving gas-rich fluid inclusions. The elemental and isotope systematics of the fluid inclusion-hosted volatile species (He, Ar, N, CO2) within the mantle xenoliths are consistent with the enrichment of the EARS SCLM by CO2-rich mantle fluids from subducted carbonate-rich material. Such CO2 enrichments (CO2/3He > 7 × 109, δ13C ~0‰) are also associated with positive δ15N values (as high as +3.4‰), reinforcing the link between the metasomatic fluids and subduction of hydrothermally altered oceanic crust. Recycled signatures are also consistent with oxygen and sulfur isotope compositions of host crystals, which are distinct from compositions typical for the depleted upper MORB-source mantle. The occurrence of recycled volatile signatures in the EARS SCLM is widespread and must therefore be associated with a large-scale mantle process currently supplying material to EARS magmas. Notably, mantle xenoliths with high 3He/4He from the Ethiopian Rift are also associated with δ15N and δ13C values similar to the composition of sediments. This suggest that recycled materials have been entrained within the deep-seated African Superplume, which supplies the EARS with both primordial and recycled volatiles.
Online veröffentlicht am 13. Dezember 2021
Gesehen am 16.01.2023